Reconsidering the life of power : ritual, body, and art in critical theory and Chinese philosophy . - Garrison, Jim, 1951- (ALBANY : STATE UNIV OF NEW YORK PR, 2021)
Offers a compelling intercultural perspective on body, art, self, and society.
Kant and the World Observer -- Arendt's Remarks on Kant -- Lĭ Zéhòu and Kant -- Hannah Arendt and Lĭ Zéhòu on Kantian Purposiveness in Human Affairs -- Conclusion -- Chapter 5 Technique in Appearance -- Preliminary Remarks: Apprehension, Appearance, and Concern -- Stiegler on Technique and Memory -- Reassessing Stiegler and Ritual Technique in Appearance -- Conclusion -- Chapter 6 Somaesthetics -- Preliminary Remarks: Somaesthetics and Subjectivation -- Somaesthetics: Rethinking Bodily Cultivation -- Somaesthetic Practice: A Resource for Expanding Subject Life or Another Means of Control? -- Confucian Perspectives on the Development of Ritual Propriety: Inside or Outside of Human Nature? -- Mencius on Human Nature and Ritual -- Xún Zĭ on Human Nature -- Xún Zi's Restricted Usefulness for Somaesthetics and the Potential Value of New Approaches to Mencius -- Assessing Somaesthetics with Regard to Mencius and Xún Zĭ -- Conclusion -- Final Thoughts -- Changing the Stakes -- Conclusion -- Notes -- Index.
eBooks on EBSCOhost
Keywords: Philosophy, Chinese; Aesthetics, Chinese; Critical theory -- China; Philosophie chinoise; Esthétique chinoise; Théorie critique -- Chine; Aesthetics; Eastern; PHILOSOPHY; Confucianism; RELIGION; Aesthetics, Chinese; Critical theory; Philosophy, Chinese; China